EKSTRAKSI PEKTIN DARI KULIT BUAH PISANG RAJA (Musa sapientum) - Farida Hanum; Irza Menka Deviliany Kaban; Martha Angelina Tarigan (Jurnal Teknik Kimia USU, 2012)
Pectin is extensively utilized by the food processors especially for conversion of low grade fruits in to good quality products like jam, jelly, marmalade, and candies. Pectin has many applications in food and pharmaceuticals products as gelling agents and stabilizers. This research aims to utilize banana peel waste (Musa sapientum) as a source of pectin. The research used a solvent extraction method using hydrochloric acid (HCl) in additional to ethanol to precipitate the pectin and the last step drying process to obtain dry pectin. The fixed variables which were used in this research were 10 grams of banana peel (Musa sapientum), 10% water content of sample, and hydrochloric acid (HCl) as a solvent. The extraction process was carried out by pH 1; 1.5, 2; the time of 70, 80, 90, 100 minutes, and the temperature of 80 oC, 90 oC. The results showed that the highest yield of the extraction was obtained at 90 oC, pH 1.5 during 80 minutes with 11.93% water content of 0.79% ash content, about 600-800mg and 4, 43% methoxyl content.